Evaluación de la calidad del agua río Algodonal, tramo Abrego-Ocaña, Norte de Santander (2019)
The physicochemical and microbiological quality of Algodonal river water was assessed by determining quality indices: ICOMI; ICOSUS, ICOpH, ICOMO and ICOTEMP. The research was developed in ten months, covering a rainy season and a dry one, where the bimodal rain regime, characteristic of the area, was used. Likewise, the relationship between the set of results and assessments that allowed the analysis of variances and behavior of the variables in each season, according to the rainfall regime, was determined. According to research results, the water quality in this section does not present any contamination, with a good water quality level, being suitable for human consumption, with previous treatment.